2020
DOI: 10.1001/jamadermatol.2020.1731
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Gene Expression Profile Tests for Prognosis in Patients With Localized Cutaneous Melanoma

Abstract: IMPORTANCEThe performance of prognostic gene expression profile (GEP) tests for cutaneous melanoma is poorly characterized. OBJECTIVE To systematically assess the performance of commercially available GEP tests in patients with American Joint Committee on Cancer (AJCC) stage I or stage II disease.DATA SOURCES For this systematic review and meta-analysis, comprehensive searches of PubMed/MEDLINE, Embase, and Web of Science were conducted on December 12, 2019, for English-language studies of humans without date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
(124 reference statements)
0
24
0
Order By: Relevance
“…The use of prognostic gene expression profiling (GEP) tests (before or after SLNB) requires further investigation across large, prospectivelyenrolled cohorts of unselected patients. Given the low probability of metastasis in stage I melanoma and a higher proportion of false-positive results, [151][152][153][154] the NCCN panel concluded that currently available GEP tests should not replace pathologic staging procedures, be used to determine SLNB eligibility, or guide clinical-decision making in this subset of patients (see ME-2A, footnote d, and ME-F 1 of 3; available in these guidelines at NCCN.org). Principles of nuclear medicine, surgery, and pathology pertaining to SLNB have also been recently revised (ME-F 2 and 3; available in these guidelines at NCCN.org).…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%
“…The use of prognostic gene expression profiling (GEP) tests (before or after SLNB) requires further investigation across large, prospectivelyenrolled cohorts of unselected patients. Given the low probability of metastasis in stage I melanoma and a higher proportion of false-positive results, [151][152][153][154] the NCCN panel concluded that currently available GEP tests should not replace pathologic staging procedures, be used to determine SLNB eligibility, or guide clinical-decision making in this subset of patients (see ME-2A, footnote d, and ME-F 1 of 3; available in these guidelines at NCCN.org). Principles of nuclear medicine, surgery, and pathology pertaining to SLNB have also been recently revised (ME-F 2 and 3; available in these guidelines at NCCN.org).…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%
“…Similarly, Gastman et al found that 31-GEP accurately identified high-risk patients who are likely to recur or die of melanoma in low-risk subgroups (e.g., sentinel lymph node-negative disease, stage I and IIA) [32]. A meta-analysis reported that 31-GEP performance varied, and was a better predictor of recurrence in stage II disease than in stage I [33]. However, a separate study suggested that there is limited cost-benefit of 31-GEP utilization in stage IIIA melanoma due to the limited survival benefit of this tool for this patient subgroup [34].…”
Section: Gene-expression Profilingmentioning
confidence: 99%
“…To determine the impact of these GEPs, and other tests, on decision to biopsy SLNs and their role in staging (see below), a large retrospective study and/or longitudinal studies will be necessary to determine how these biomarkers predict clinically meaningful outcomes like distant metastasis freesurvival and all-cause mortality. Meta-analysis of existing studies has demonstrated that currently available GEP tests have limited ability to prognosticate recurrence in early stage melanomas (96). Due to the cost of conducting such trials, in terms of economic considerations and irreplaceable patient samples, the melanoma community will need to identify and prioritize the coordinated validation of only the most promising biomarker assays.…”
Section: Stratifying Risk Of Lymph Node Metastasismentioning
confidence: 99%